Tổng quan các nghiên cứu về phương pháp giáo dục đạo đức môi trường cho học sinh - Đoàn, Thị Thoa (Tạp chí Giáo dục, 2025)
Environmental ethics education is increasingly receiving attention in the context of many countries promoting education for sustainable development. This article aims to present some concepts of environmental ethics education and approaches to teaching environmental ethics to secondary school students through a comprehensive literature review. Based on the overview, the article clarifies effective teaching methods such as: ethical challenge games, the Socratic method, situation handling and practical experience - approaches that have been proven to help students not only acquire knowledge but also form critical thinking, social emotions and positive ethical behavior towards the environment. The study is significant in systematizing theories and methods of environmental ethics education, helping to orient future studies. In practice, the study supports teachers and educational administrators in effectively applying teaching methods, contributing to raising environmental awareness among secondary school students.